2016
DOI: 10.9744/jak.18.2.92-104
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Emission Disclosure: Studi pada Perusahaan Manufaktur Indonesia

Abstract: ABSTRAKPenelitian ini bertujuan untuk menguji faktor-faktor yang berpengaruh terhadap pengungkapan emisi karbon. Faktor yang diuji di dalam penelitian ini meliputi ukuran perusahaan, profitabilitas, kompetisi, pertumbuhan, rasio utang pada ekuitas, dan reputasi Kantor Akuntan Publik. Metode yang digunakan untuk mengukur seberapa luas pengungkapan emisi karbon mengadopsi dari check list yang dikembangkan berdasarkan lembar permintaan yang diperoleh dari Carbon Disclosure Project (CDP). Sampel penelitian ini dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
1
38

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(99 citation statements)
references
References 20 publications
3
57
1
38
Order By: Relevance
“…The theory used as a fundamental of carbon emission disclosure is the theory of legitimacy [19]. According to Berthelot and Robert (2011), environmental disclosure is one among many ways of organisations to gain legitimacy.…”
Section: The Impact Of Carbon Emission Disclosure and Financial Perfomentioning
confidence: 99%
See 2 more Smart Citations
“…The theory used as a fundamental of carbon emission disclosure is the theory of legitimacy [19]. According to Berthelot and Robert (2011), environmental disclosure is one among many ways of organisations to gain legitimacy.…”
Section: The Impact Of Carbon Emission Disclosure and Financial Perfomentioning
confidence: 99%
“…According to Berthelot and Robert (2011), environmental disclosure is one among many ways of organisations to gain legitimacy. The theory of legitimacy focuses on the relationship between a company and society through the regulations made by the government [19]. When there is a difference between the company and society, which is related to the value held by the 'legitimation gap', then at that time, the company's legitimacy is in a threatened position and may affect its ability to continue its business activities.…”
Section: The Impact Of Carbon Emission Disclosure and Financial Perfomentioning
confidence: 99%
See 1 more Smart Citation
“…Good corporate performance will affect how fast company responses to the issue. Companies with better performance will have greater ability for disclosure and having more details disclosure area as well (Roberts, 1992 in[17]). Based on the theory and results of previous research, it can be concluded that companies with good profitability will be able to provide additional employee or financial resources for voluntary disclosure.…”
mentioning
confidence: 99%
“…Second, companies with low profitability take advantage of environmental disclosure for legitimacy purposes. Conversely, companies with high profitability do not need to expand their environmental disclosure as it may disrupt financial achievement of the company[17].…”
mentioning
confidence: 99%